Tuning the Charge Transfer Dynamics of the Nanostructured GaN Photoelectrodes for Efficient Photoelectrochemical Detection in the Ultraviolet Band. (7th May 2021) - Fang, Shi; Wang, Danhao; Wang, Xiaoning; Liu, Xin; Kang, Yang; Yu, Huabin; Zhang, Haochen; Hu, Wei; He, Jr‐Hau; Sun, Haiding; Long, Shibing
Abstract: The intriguing surface sensitivity of the single‐crystalline semiconductor nanowires offers tremendous opportunity in tuning the physical properties of nanophotonic and nanoelectronic devices for versatile applications. Particularly, in the pursuit of emerging photoelectrochemical (PEC)‐type devices, significant efforts have been devoted to understanding the charge transfer dynamics between the nanowires and the electrolyte. Here, a PEC‐type ultraviolet photodetector consisting of GaN p ‐ n junction nanowires as photoelectrodes is constructed. It is found that two competing charge transport processes at the nanowires' surface as well as in the p ‐ n junction co‐determine the photoresponsive behavior of the device. Furthermore, the surface platinum (Pt) decoration has successfully tuned the charge transfer dynamics by enhancing the charge transport efficiency at the surface, resulting in a twenty‐fold increase of the photocurrent compared to the pristine GaN nanowires. Theoretical calculations reveal that the newly formed electronic states at the Pt/GaN interface account for the improved charge transfer at the surface, and the optimal hydrogen adsorption energy contributes to the boosted PEC reaction rate. The synergy of these two effects uncover the underlying mechanism of the high photoresponse of the constructed Pt/GaN‐nanowires‐based PEC photodetectors. Abstract : GaN nanowires are used as a photoelectrode to build a photoelectrochemical‐type ultraviolet photodetector. A new dynamic charge transfer behavior is discovered. The decoration of platinum nanoparticles boosts the charge transfer and chemical reactions at the GaN nanowires' surface. The resulting photocurrent is improved by more than one order of magnitude.